(untitled) (Bangladesh Journal of Anatomy, 2011)
Context: The thyroid is a brownish red, highly vascular earliest endocrine glandular structure appears in mammal. The size of thyroid gland varies considerably with age, sex, physiologic state, race and geographical location. It is larger and heavier in females than in males, and it hypertrophies during menstruation and pregnancy. So this study is to carry out the macroscopic architecture of thyroid gland of different age groups in Bangladeshi people to establish a normal standard. Study design: Descriptive cross-sectional study. Place and period of study: Department of Anatomy, Sylhet M. A. G. Osmani Medical College, Sylhet, from July 2006 to June 2007. Materials: The study was carried out on 43 autopsied human thyroid glands aged 5 to 65 years. Thyroid glands were collected from unclaimed dead bodies autopsied in morgue of Sylhet M. A. G. Osmani Medical College, Sylhet. Methods: The collected specimens were divided into age group A (20 years and below), group B (21 to 50 years) and group C (above 50 years). All specimens were examined morphologically by fine dissection method. Result: The mean weight and volume of the thyroid gland was 13.27 ± 5.82 gm and 11.62 ± 4.76 ml respectively which are significant (p<0.01). Conclusion: From observation and results it reached conclusion that evidenced by weight and volume, the size and glandular structure gradually increase with age up to adolescence, remain stable in young and middle aged adult then slowly decline in old age. The present study will help to increase the information pool on the anatomy of thyroid gland of Bangladeshi people. To establish a normal standard for Bangladeshi people, further studies with large samples from different zones including goitre endemic zones of the country are suggested. Keywords: weight, volume, thyroid gland, postmortem. DOI: 10.3329/bja.v8i2.7020 Bangladesh Journal of Anatomy July 2010, Vol. 8 No. 2 pp. 72-75